2017
DOI: 10.1007/s41030-017-0043-5
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Safety and Efficacy of Inhaled Corticosteroids in the Management of Asthma

Abstract: Asthma is a chronic inflammatory disease characterized by symptoms of cough, dyspnea, chest tightness, and wheeze. Inhaled corticosteroids (ICS) have been recommended as initial therapy in the treatment of persistent asthma in all guidelines, as they have been shown to reduce morbidity and mortality. However, high-dose regimens and long-term use of ICS may be associated with a variety of side effects, similar to those observed with systemic corticosteroid therapy. These side effects include impaired growth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 144 publications
1
48
0
2
Order By: Relevance
“…[37][38][39] It is best practice to review ICS dose and use the lowest dose possible to maintain asthma control. 40 We also found that the rise in OCS cost was mainly driven by a steep increase in price of hydrocortisone tablets from 2008 onwards; and BP prescribing went up as BP cost went down after 2005.…”
Section: Discussionmentioning
confidence: 58%
“…[37][38][39] It is best practice to review ICS dose and use the lowest dose possible to maintain asthma control. 40 We also found that the rise in OCS cost was mainly driven by a steep increase in price of hydrocortisone tablets from 2008 onwards; and BP prescribing went up as BP cost went down after 2005.…”
Section: Discussionmentioning
confidence: 58%
“…The use of high doses of ICS for prolonged periods increases the risk of systemic adverse effects, such as reduction of bone mineral density, respiratory infections (including tuberculosis), cataracts, glaucoma, and suppression of the hypothalamic-pituitary-adrenal axis. (1,(36)(37)(38)(39)…”
Section: Icsmentioning
confidence: 99%
“…Prevalensi dan keparahan penyakit alergi terus meningkat secara global, terutama di negara dengan pendapatan rendah sampai menengah 1 . Penggunaan terapi alergi jangka panjang selain dapat menyebabkan efek samping berupa sindroma Cushing juga membebani penderita dari segi ekonomi 2 . Daun jambu biji (Psidium guajava) secara tradisional digunakan untuk mengobati inflamasi, diabetes, hipertensi, luka, nyeri, dan demam 3 .…”
Section: Pendahuluanunclassified